The The potential of words to become swearing: An ethno semantic study - Amilia, Fitri; Astri Widyaruli Anggraeni; Anita Fatimatul Laeli; Kemal, Edwar (BAHASTRA, 2024)
This research aims to describe the potential of words as swear words through an ethno semantic study. This research differs from other swearing studies examining the form and meaning of swear words. This study presents the potential of words to become swear words. This research employs a phenomenological approach. Swear words are expressive words that convey emotions and are easily found in both oral and written forms, whether directly or on social media. The data collection technique for swear words is documentation. The steps in documentation include recording sentences that contain swear words and classifying them based on the characteristics of swear words. The analysis technique for swear words uses conceptual meaning analysis. Based on the classification of the data, the words are analyzed for their components of meaning, both lexically and in terms of meaning derived from cultural associations and societal thought. Thus, the findings reveal the potential of each lexical word to become a curse word using an ethno semantic approach. Through an ethno semantic study, two potentials exist for words to become swear words. First, conceptual meaning is added due to the speakers' ideas, thoughts, knowledge, and culture. Second, there is a loss of conceptual meaning in the form of functional components in the lexical meaning of a word.